Rescue of Influenza A Virus from Recombinant DNA - Fodor, Ervin (American Society for Microbiology, 1999)
We have rescued influenza A virus by transfection of 12 plasmids into Vero cells. The eight individual negative-sense genomic viral RNAs were transcribed from plasmids containing human RNA polymerase I promoter and hepatitis delta virus ribozyme sequences. The three influenza virus polymerase proteins and the nucleoprotein were expressed from protein expression plasmids. This plasmid-based reverse genetics technique facilitates the generation of recombinant influenza viruses containing specific mutations in their genes.